THE INFLUENCE OF FACEBOOK SOCIAL MEDIA USE ON EMPLOYEE WORK BEHAVIOR AT WONOSARI CAMAT OFFICE - Andrianus Eko Saputra; Ikram Muhammad; Maman Musa (Jurnal Ilmu Manajemen dan Bisnis, 2023)
This study has a formulation that is: "Is there any effect of using social media on the work behavior of employees at the Wonosari sub-district office?". To answer this research question, an associative type of research is used with a quantitative approach with social media facebook as a variable (X) and employee work behavior as a variable (Y). premiere data collection was used through questionnaires which were distributed to 30 respondents with saturated sampling technique or all members of the population, namely the Wonosari sub-district office employees as sample members. The results of data collection were then analyzed using correlation and regression analysis techniques with the help of the SPSS version 17 application program. The results showed that there was no significant effect of social media on the work behavior of employees at the Wonosari sub-district office, with an influence contribution of 7.70% and the rest explained by regulatory factors. Thus, the researcher's hypothesis which states that there is a significant negative influence of social media on employee work behavior is proven and unacceptable, so that if the control of the use of social media is good, the work behavior of employees in the Wonosari sub-district office will also improve. Therefore, it is suggested that the leader can control the individual work behavior of employees in using excessive social media by conducting an objective and fair assessment process for all employees by including the aspects of managerial competence needed. So that the merit system in employee management can really be realized in order to realize a more professional government bureaucracy. The work behavior assessment can be carried out by detailing thoroughly and in detail about aspects of work behavior, including performance and leadership aspects such as teamwork skills, communication skills, initiative, and work responsibilities. So that the expected merit system of employee management can actually be realized in the Regional Government of Boalemo Regency, especially Wonosari District in order to realize a professional government bureaucracy. The work behavior assessment can be carried out by detailing thoroughly and in detail about aspects of work behavior, including performance and leadership aspects such as teamwork skills, communication skills, initiative, and work responsibilities. So that the expected merit system of employee management can actually be realized in the Regional Government of Boalemo Regency, especially Wonosari District in order to realize a professional government bureaucracy. The work behavior assessment can be carried out by detailing thoroughly and in detail about aspects of work behavior, including performance and leadership aspects such as teamwork skills, communication skills, initiative, and work responsibilities. So that the expected merit system of employee management can actually be realized in the Regional Government of Boalemo Regency, especially Wonosari District in order to realize a professional government bureaucracy.